Analysis of Modern PR Strategies in the Show Business Industry - Balan, Anastasia; Krupa, Oksana (Socio-Cultural Management Journal, 2024)
Introduction. In the modern world, the show business industry is central to the cultural and entertainment life of society. Show business is an important mechanism for shaping social stereotypes, influencing mass consciousness, creating trends and defining cultural values. Professional PR has become an integral part of successful activities in the show business industry. It plays a key role in building a positive image of artists, production companies, film companies, music bands and other market participants. Purpose and methods. The purpose of the study is to theoretically analyze modern PR strategies in the show business industry, to study and understand modern approaches to PR communications in this area, taking into account technological, social and economic trends. The methodological basis is the systemic and interdisciplinary approaches, as well as methods of general scientific, terminological, expert, observation and comparison, critical analysis, abstract and logical modeling. Results. The types of PR, the essence and the role of PR strategies in the show business industry are defined. The essence of using social media as a PR tool is revealed. Modern PR strategies in the show business industry are substantiated. Conclusions. The study indicates that factors such as authenticity, consistency and cooperation with influential personalities are of great importance in modern PR strategies. In addition, the effectiveness of PR strategies is also determined by the ability to adapt to changes in society, responding to challenges and trends. There is a need to integrate PR strategies into the overall marketing strategy of companies and artists, which will ensure their consistency and interaction with other types of marketing.